rhetorical and argumentative means in the german–polish discourse ahead of the 2023 polish parliamentary elections - Dąbrowska-Burkhardt, Jarochna (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The political and discourse linguistic article identifies and analyzes the functioning of the underlying linguistic and multimodal patterns in the transnational discourse on the parliamentary elections held in Poland on 15 October 2023. The focus of the investigation is an image of Germany that is conveyed in Poland’s public television programs during the 2023 election campaign. It is not only constituted verbally, but also represents a complex semiotic system. The applied methodology of discourse analysis makes it possible to describe concrete linguistic units and to clarify their conceptual-semantic nature and their function in the discourse.
Keywords: media discourse; German-Polish discourse; politolinguistics; linguistic discourse analysis; argumentation patterns